Accounting for Retail Land Sales. - Cerf, Alan Robert (The Accounting Review, 1975)
This article presents an analysis of the provisions of the "Accounting for Retail Land Sales" guide, published by the a committee on land development companies, established by the American Institute of Certified Public Accountants (AICPA). This committee was established when the problems of accounting for land development companies began to receive considerable attention in financial publications and in non-accounting journals. The AICPA committee presented an exposure draft which required, among other things, that land subdivision companies postpone recognition of revenue from installment contracts until at least a 10% down payment was collected and that a company's collection experience met certain requirements. The guide provides for a modified accrual method to be used if certain conditions are met. Otherwise the installment sales method should be employed. The identifying characteristic of the land development company is the acquisition of large tracts of unimproved land for subdivision into lots for sale to widely dispersed retail customers through intensive marketing programs.